Assessment of Lifestyle and Financial Experience on Student Financial Management Behavior - Rosita, Ita; Ruwandini Fitri, Oktavandila; Sobiyah, Sobiyah; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
A country's high level of finance will encourage the development of its economy. Internal and external factors cause high and low financial management behavior. This study aims to develop a model that examines the three variables that the author has analyzed to determine the factors that can improve student financial management behavior. This study used an associative descriptive quantitative method with a population of 73 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The first hypothesis is that lifestyle significantly affects student financial management behavior, and the second hypothesis is that financial experience partially impacts student management behavior; the third hypothesis is that lifestyle and financial expertise together can affect financial management behavior. This research is expected to make theoretical contributions to the literature in this context, including in the context of economic and banking management.